STRATEGI GURU DALAM MENERAPKAN METODE MUROJA’AH UNTUK MENINGKATKAN KUANTITAS HAFALAN AL-QUR’AN PADA SD ISLAM TERPADU FITRAH INSANI SUNGAI BAHAR MUARO JAMBI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe teachers’ strategies in implementing the muroja’ah method to improve students’ Qur’an memorization quantity at SD Islam Terpadu Fitrah Insani Sungai Bahar. The study is based on the issue of students’ memorization achievements that have not yet met the expected curriculum targets, as well as several challenges such as limited learning time, differences in students’ memorization abilities, and the non-optimal implementation of muroja’ah strategies by teachers. This research employs a qualitative approach using a descriptive-analytical method. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that teachers apply various muroja’ah strategies, including daily repetition, paired muroja’ah, classical muroja’ah, and tasmi’ with teachers; however, these strategies are not yet fully systematic or well-structured. Supporting factors include the religious school environment and the motivation of some students, while inhibiting factors consist of limited time allocation, lack of parental involvement at home, and the absence of a standardized muroja’ah guideline. This study is expected to contribute to the development of more effective tahfidz learning strategies and provide valuable input for schools in improving the quality and quantity of students’ Qur’an memorization.